Urethral dosimetry constraints in 125-I permanent prostate brachytherapy used as boost to external radiotherapy (Revista de Física Médica, 2010)
With 125-I monotherapy in permanent brachytherapy implants, the recommendation is to deliver to the urethra less than 150% of the prescribed dose, 145 Gy, that is a limit of 217.5 Gy. However, there are not recommendations in the case of the brachytherapy boost.At our hospitals, permanent brachytherapy implants are used as a 108 Gy boost in intermediate risk patients with prostate carcinoma, which have undergone an external beam radiotherapy course ranging between 45 and 50.4 Gy.The purpose of this work is to present a simple radiobiologically-based analysis performed in order to obtain the urethral dose limit in permanent prostate brachytherapy boost.The linear-quadratic model has been used to determine the biologically effective dose, analysing the results for different dose/fraction, t1/2 and alfa/beta values. Assuming 46 Gy delivered by external beam radiotherapy, it is found that a limit value of 145 Gy, corresponding to the isodose level of 135% of the prescribed dose, is adequate. The results for a ten patients sample are shown in order to illustrate the values that are obtained in clinical practice.In conclusion, we present the method employed to find the urethral dose limit in the case of the combination of external beam radiotherapy and permanent 125I seeds brachytherapy boost implants.